Comparative Analysis of AC and DC Distribution System with Respect to Harmonic Distortion Considering Daily Load Profile - Faisal Shahzad (Pakistan Journal of Engineering & Technology, 2020)
Electrical energy is the most efficient and the cleanest form of energy at the moment that is being transmitted and distributed amongst end-users. From its earlier days, the AC system was preferred as an economical solution for transmission and distribution. However, the development in the power electronics technology and the evolution of highly efficient power electronic converters have established the resurgence of DC power system. Furthermore, the trend is shifting towards DC loads as various energy efficient appliances, such as DC inverter air conditioners, operate on DC nowadays. This further advocates the shift towards the DC power system. This research works is an effort to perform the comparative analysis of AC Distribution System (ACDS) and DC Distribution System (DCDS), with regards to power quality and harmonic distortion in particular. The comparison is performed considering load profile and load variation on daily basis. Simulations are performed in MATLAB. It has been concluded at the end that ACDS is better than DCDS in terms of power quality as total harmonic distortion of the DCDS under the same loading and same load variation during the whole day was significantly higher than that of ACDS.